Keterkaitan Al-Qur'an dan Ilmu Alam: Perspektif dalam Pembelajaran Pendidikan Agama di Sekolah - Muamar Muamar; Kartimi Kartimi; Yayan Rahtikawati (Departement of Mathematics Education, 2024)
This paper aims to explore the relationship between the teachings of the Qur'an and natural sciences, and how this relationship can be implemented in religious education learning in schools. The Qur'an, as the main source of teachings in Islam, not only provides moral and spiritual guidance, but also touches on many natural phenomena that can be explained through science. This article analyzes verses in the Qur'an related to the universe, as well as how religious education in schools can combine religious values ​​and scientific knowledge, in order to shape students' broad-minded characters. This study uses a qualitative approach with literature studies as the main methodology. The results of the study indicate that the integration of religious teachings and science is not only beneficial for scientific understanding, but also strengthens students' spiritual beliefs. Learning based on the relationship between the Qur'an and natural sciences can create a more holistic understanding, and foster a sense of responsibility towards the environment.